2004
DOI: 10.1148/radiol.2301020269
|View full text |Cite
|
Sign up to set email alerts
|

Improved Detection of Focal Liver Lesions at MR Imaging: Multicenter Comparison of Gadoxetic Acid–enhanced MR Images with Intraoperative Findings

Abstract: MR imaging with gadoxetic acid is safe and improves lesion detection and localization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
298
6
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 380 publications
(315 citation statements)
references
References 28 publications
(31 reference statements)
10
298
6
1
Order By: Relevance
“…Uptake of about 50% of injected Gd-EOB-DTPA is started by the anionic transporter protein of hepatocytes following contrast agent administration and leads to intracellular accumulation, and thus increased signal intensity of liver parenchyma on delayed T 1 -weighted MR images. The remaining 50% of injected Gd-EOB-DTPA is excreted through the renal system (20,22). In this study, there was no significant difference in mean SIR of the liver in the portal phase between Gd-EOB-DTPA and Gd-DTPA.…”
Section: Figurecontrasting
confidence: 43%
See 1 more Smart Citation
“…Uptake of about 50% of injected Gd-EOB-DTPA is started by the anionic transporter protein of hepatocytes following contrast agent administration and leads to intracellular accumulation, and thus increased signal intensity of liver parenchyma on delayed T 1 -weighted MR images. The remaining 50% of injected Gd-EOB-DTPA is excreted through the renal system (20,22). In this study, there was no significant difference in mean SIR of the liver in the portal phase between Gd-EOB-DTPA and Gd-DTPA.…”
Section: Figurecontrasting
confidence: 43%
“…In several clinical studies, this contrast agent has been demonstrated to provide differential diagnostic information comparable to nonspecific gadolinium chelates (8,14) and to improve the detection of focal liver lesions due to its highly specific uptake by hepatocytes (20). In addition, Gd-EOB-DTPA allows assessment of arterial perfusion during the vascular phase of dynamic imaging, and may be adapted to the other abdominal organs as well as liver, such as with Gd-DTPA.…”
Section: Discussionmentioning
confidence: 99%
“…Lesions that were identified only on hepatobiliary phase images were mostly small and showed some enhancement on dynamic images. However, those lesions showed marked hypointensity in the strongly enhanced background liver parenchyma (29). The improvement in lesion conspicuity on hepatobiliary phase imaging is supported by the significant increase in liver-to-lesion SR on both 10-minute and 20-minute delayed hepatobiliary phase images.…”
Section: Discussionmentioning
confidence: 74%
“…Gadoxetic acid can effectively be used in dynamic and liver-specific static MRI with accurate delineation, classification, and characterization of liver tumors, in which excellent sensitivity and characterization for hepatocellular lesions are provided (10,12,14,(16)(17)(18)(19). The diagnosis of early HCC is one of the potential indication (20,21).…”
Section: Discussionmentioning
confidence: 99%